Upaya Meningkatkan Keterampilan Bowling Fast Cricket Berbasis Media Terhadap Mahasiswa Klub Olahraga Prestasi (KOP) Cricket Universitas Negeri Jakarta - Rahmawati Dwi Pangestu; Mastri Juniarto; Iwan Setiawan; Andi Hasriadi Hasyim (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2023)
This study aims to determine the improvement of media-based fast bowling cricket skills in students of The Jakarta State University cricket achievement Sports Club. This study was conducted with the research method Action Research (Action) model Kemmis and Taggart. There are 6 media used for the treatment of fast bowling ball reflections, so it is worth testing. This research was conducted on the students of club Olahtaga Prestasi (KOP) cricket Universitas Negeri Jakarta with the number of 26 students. Treatment this study uses a cycle system that is carried out for two cycles by placing the target media in the area of the ball reflection (good length). From the given treatment is followed by an assessment instrument using a colored carpet with a variety of points. A good standard result in a fast bowling bowler is 75%. The results of the assessment instrument in the pre-cycle (Pre-Test) are less than the standard in which the same treatment is required again. In the first cycle results in an increase in the bounce of the ball. The results of the second cycle has increased more than the first cycle, the results of the instrument assessment of the average student exceeds the standard value determined by the researcher.